Two new species of the genus Pseudostenophylax Martynov (Trichoptera: Limnephilidae) from the Indian Himalaya - Parey, Sajad H.; Saina, Malkiat S.; Pandher, Manpreet S. (Zootaxa, 2013)
Two new species of the genus Pseudostenophylax Martynov 1909 from the Indian Himalaya are described and illustrated. These include P. himachalica sp. n. from Sathrundi (Himachal Pradesh) and P. gulmargensis sp. n. from Gulmarg (Jammu & Kashmir), both belonging to the P. aniketos Group. With these two additions, Pseudostenophylax is now represented inIndia by 25 species.